Survey of major trauma centre preparedness for mass casualty incidents in Australia, Canada, England and New Zealand. (April 2020) - Gabbe, Belinda J.; Veitch, William; Curtis, Kate; Martin, Kate; Gomez, David; Civil, Ian; Moran, Chris; Teague, Warwick J.; Holland, Andrew J.A.; Lecky, Fiona; Fitzgerald, Mark; Nathens, Avery; et al.
Abstract: Background: Mass casualty incidents (MCIs) are increasing. Trauma centres play a key role in MCIs due to their readiness and expansive multidisciplinary expertise for injury management. Previous studies have shown deficiencies in trauma centre disaster preparedness. The aim of this study was to describe the current disaster preparedness of Major Trauma Centres (MTCs) in Australia, Canada, England and New Zealand. Methods: A cross-sectional survey of all ( n = 82) MTCs was undertaken. The anonymous survey collected data about disaster preparedness in nine key areas. Respondents were encouraged to consult appropriately at their centre to provide an accurate representation of their centre's preparedness. Findings: Responses were received from 69 (84%) centres; 61 completed all questions. 91% had a disaster preparedness committee and 80% had an all-hazards emergency plan. 79% had held an MCI drill in the past 2 years. 54% reported a system in place to calculate maximum capacity, but testing of surge capacity was uncommon. 55% reported the presence of stored resources for an MCI and 58% had a database of staff trained in Emergency Management. 74% had a training and education plan available for staff involved in an MCI and a plan for professional debriefing of staff post-MCI, while 62% had a post-disaster employee assistance programme. Most centres had appropriate back-up communication, safety and security plans. Interpretation: The disaster preparedness of MTCs was high for communication, safety and security but there was clear need for improvement in other areas including surge capacity, human resources and post-disaster recovery.